Peningkatan Pertumbuhan Ekonomi Melalui Potensi Wisata Halal - ulya, faridatul (Jurnal Perbankan Syariah, 2023)
This research focuses on potential opportunities for halal tourism to increase economic growth. This study uses a qualitative literature research approach by tracing primary sources in the form of articles or journals with themes that match the title. The results of the study show that the opportunity for halal tourism is very large, considering that Indonesia is a country with a majority Muslim population, and the increasing number of visits in halal tourism will be better and related to economic growth in Indonesia which is related to plans for realizing sustainable development (SDGs).